PENGEMBANGAN MODUL PEMBELAJARAN MIKRO BERBASIS INSTRUCTIONAL APPROACH - Rosita Ambarwati; Samsul Arifin; Dwi Rosita Sari (Jurnal Penelitian LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) IKIP PGRI MADIUN, 2014)
Departing from the results of previous research that has developed an innovative model of microteaching and need-analysis results that English Department requires the existence of an effective instructional approach based-microteaching module. Furthermore, this module will improve the English Department students ability in microteaching. This research design is Research and Development developed by Borg and Gall The research conducted to English Department students of IKIP PGRI Madiun. The numbers of the students were 298 students from February to September 2014. The qualitative data in this study were analyzed by three flows of activity that comprises a sequence of data reduction, the data display, and conclusion drawing or verification, while the quantitative data (performance test results) was analyzed by t-test to determine its effectiveness. The results showed thatthe format and content of the module are good. It is done by two validators (English language learning experts and graphic designer). In addition, the application of microteaching module gives an easier way for lecturers in coaching against students in preparing lesson plans, implementing learning and evaluate learning outcomes. Last, the application of microteaching module is able to enhance basic skills of teaching.